Exploring Teachers' and learners' Attitudes towards the Effectiveness of Genre- Based Approach on Enhancing Writing Skills. The Case of 3rd Year Bachelor’s EFL Students at The University of Souk-Ahras - Djamel MERABTI (My University, 2024)
Abstract Writing proficiency is paramount for success in higher education, enabling students to articulate thoughts with clarity, coherence, and persuasion within formal frameworks. While traditional teaching methods focus on vocabulary, grammar, and sentence structure, they often overlook the broader context of academic genres and their conventions. Genre-Based Approaches (GBA) have emerged as an alternative, emphasizing the analysis and instruction of specific writing types within the framework of systemic functional linguistics (SFL). This study explores EFL teachers' and learners' attitudes towards the effectiveness of GBA in improving the writing skills of third year Bachelor’s EFL students at the University of Mohamed Cherif Messaadia, Souk-Ahras. Employing a mixed-methods approach, quantitative data is gathered through a questionnaire administered to 21 third-year English students, probing their perceptions of GBA's impact. Qualitative insights are derived from semi-structured interviews with two teachers. Findings reveal positive attitudes among both teachers and students towards GBA's efficacy in enhancing writing skills. Participants perceive GBA as superior to traditional methods, particularly in improving organization, coherence, and the use of appropriate language for specific genres. However, some challenges have been identified, including the time-intensive nature of genre analysis, the need for extensive teacher training, and difficulties in multi-genre assessment. ---------------------- ‫االستيعاب‬‫الكتابي‬ ‫أمر‬ ‫حاسم‬ ‫لنجاح‬ ‫التعليم‬ ‫العالي‪،‬‬ ‫حيث‬ ‫يمكن‬ ‫للطالب‬ ‫التعبير‬ ‫عن‬ ‫أفكارهم‬ ‫بوضوح‬ ‫وتراب‬ ‫ط‬‫وإقن‬ ‫اع‬‫ضمن‬ ‫إطارات‬‫رسمية‪.‬‬ ‫في‬ ‫حين‬ ‫تركز‬ ‫األساليب‬ ‫التقليدية‬ ‫للتدريس‬ ‫على‬ ‫المفردات‬ ‫والقواعد‬ ‫النحوية‬ ‫وبنية‬ ‫الجملة‬ ‫‪،‬‬‫إال‬ ‫أ‬ ‫نها‬‫في‬ ‫كث‬ ‫ير‬‫من‬ ‫األحيان‬‫تغفل‬ ‫السياق‬ ‫األوسع‬ ‫ألنواع‬ ‫األدب‬ ‫األكاديمي‬ ‫ومعاييرها‪.‬‬ ‫ظهر‬ ‫النهج‬ ‫القائم‬ ‫على‬ ‫األنواع‬ ‫(‬ ‫‪GBA‬‬‫)‬‫ك‬ ‫بديل‪،‬‬‫مع‬ ‫التركيز‬ ‫على‬‫تحليل‬ ‫وتعليم‬ ‫أنواع‬ ‫الكتابة‬ ‫المحددة‬ ‫ضمن‬ ‫إطار‬ ‫اللغويات‬ ‫الوظيفية‬ ‫النظامية‬ ‫(‬ ‫‪SFL‬‬‫)‪.‬‬‫تستكشف‬ ‫هذه‬ ‫ال‬ ‫دراسة‬‫الحالية‬ ‫آراء‬ ‫معلمي‬‫ومتعلمي‬ ‫اإلنجليزية‬ ‫كلغة‬ ‫أجنبية‬ ‫(‬ ‫‪EFL‬‬‫)‬‫تجاه‬ ‫فعالية‬ ‫‪GBA‬‬ ‫في‬ ‫تحسين‬ ‫مهارات‬ ‫الكتابة‬ ‫لطالب‬ ‫السنة‬ ‫ا‬ ‫لثالثة‬‫‪EFL‬‬ ‫في‬ ‫جامعة‬‫محمد‬ ‫شريف‬ ‫مس‬ ‫ا‬‫عدية‪،‬‬ ‫سوق‬ ‫أهراس‪.‬‬ ‫باستخدام‬ ‫نهج‬ ‫األساليب‬ ‫المختلطة‪،‬‬ ‫يتم‬ ‫جمع‬ ‫البيانات‬ ‫الكمية‬ ‫من‬ ‫خ‬ ‫الل‬‫اس‬ ‫تبيان‬‫أُد‬ ‫رج‬ ‫على‬‫‪21‬‬ ‫طالبًا‬ ‫في‬ ‫السنة‬ ‫الثالثة‬ ‫من‬ ‫طالب‬ ‫اللغة‬ ‫اإلنجليزية‪،‬‬ ‫يستجوب‬ ‫تصوراتهم‬ ‫لتأثير‬ ‫‪GBA‬‬ ‫‪.‬‬‫يتم‬ ‫ا‬ ‫لحصول‬‫ع‬ ‫لى‬‫رؤى‬ ‫نوعية‬ ‫من‬‫المقابالت‬ ‫شبه‬ ‫الهيكلية‬ ‫مع‬ ‫مدرسين‬ ‫اثنين‪.‬‬ ‫تكشف‬ ‫النتائج‬ ‫عن‬ ‫توجهات‬ ‫إيجابية‬ ‫لدى‬ ‫كل‬ ‫من‬ ‫المعلمين‬ ‫وا‬ ‫لطالب‬‫ن‬ ‫حو‬‫فعالية‬ ‫‪GBA‬‬‫في‬ ‫تعزيز‬ ‫مهارات‬ ‫الكتابة‪.‬‬ ‫ينظر‬ ‫المشاركون‬ ‫إلى‬ ‫‪GBA‬‬ ‫على‬ ‫أنها‬ ‫أفضل‬ ‫من‬ ‫األساليب‬ ‫التقليدية‪،‬‬ ‫خاصة‬ ‫ف‬ ‫ي‬‫تحسين‬ ‫التنظيم‬‫والترابط‬ ‫واست‬ ‫خدام‬‫اللغة‬ ‫المناسبة‬ ‫ألنواع‬ ‫معينة‪.‬‬ ‫ومع‬ ‫ذلك‪،‬‬ ‫تم‬ ‫تحديد‬ ‫بعض‬ ‫التحديات‪،‬‬ ‫بما‬ ‫في‬ ‫ذ‬ ‫لك‬‫طبي‬ ‫عة‬‫التحلي‬ ‫ل‬‫الزمني‬ ‫المكثف‬‫لألنواع‪،‬‬ ‫والحاجة‬ ‫إلى‬ ‫تدريب‬ ‫مع‬ ‫ّ‬ ‫م‬‫ق‬‫للمعلمين‬ ‫‪،‬‬‫وصعوبات‬ ‫التقييم‬ ‫متعدد‬ ‫األنواع‬ ‫‪. ------------------- Resumé La maîtrise de l'écriture est primordiale pour réussir dans l'enseignement supérieur, permettant aux étudiants d'articuler leurs pensées avec clarté, cohérence et persuasion dans des cadres formels. Alors que les méthodes d'enseignement traditionnelles se concentrent sur le vocabulaire, la grammaire et la structure des phrases, elles négligent souvent le contexte plus large des genres académiques et de leurs conventions. Les approches basées sur les genres (ABG) ont émergé comme une alternative, mettant l'accent sur l'analyse et l'enseignement de types d'écriture spécifiques dans le cadre de la linguistique fonctionnelle systémique (LFS). Cette étude actuelle explore les attitudes des enseignants et des apprenants en anglais langue étrangère (EFL) à l'égard de l'efficacité des ABG dans l'amélioration des compétences en écriture des étudiants de troisième année en anglais à l'Université Mohamed Cherif Messaadia, Souk-Ahras. En utilisant une approche mixte, des données quantitatives sont collectées via un questionnaire administré à 21 étudiants de troisième année en anglais, sondant leurs perceptions de l'impact des ABG. Des informations qualitatives sont obtenues à partir d'entretiens semi-structurés avec deux enseignants. Les résultats révèlent des attitudes positives tant chez les enseignants que chez les étudiants à l'égard de l'efficacité des ABG dans l'amélioration des compétences en écriture. Les participants perçoivent les ABG comme supérieurs aux méthodes traditionnelles, notamment pour améliorer l'organisation, la cohérence et l'utilisation d'un langage approprié pour des genres spécifiques. Cependant, certains défis ont été identifiés, notamment la nature chronophage de l'analyse des genres, la nécessité d'une formation approfondie des enseignants et les difficultés liées à l'évaluation multi-genres.